Bipolaris sorokiniana of barley: infection behaviour in different members of Poaceae - BASHYAL, B.M.; CHAND, RAMESH; KUSHAWHA, CHANDA; JOSHI, A.K.; KUMAR, SUMIT (Indian Phytopathology, 2011)
Host range and infection behaviour of Bipolaris sorokiniana of barley was studied in wheat, barley, rice, phalaris, maize, pearlmillet and sugarcane. B. sorokiniana of barley varied in percent germination, germination behaviour, germ tube length and number of appressoria formation in different hosts. Growth of pathogen was arrested at appressoria formation stage in sugarcane and it could not infect the host. Further accumulation of less cell wall bound phenolics (4-hydroxybenzoic acid, vanillic acid, 4-hydroxybenzaldehyde, vanillin and 4-coumaric acid) and phenylalanine ammonia lyase (PAL) in barley and wheat indicated the role of these compounds in conferring resistance against B. sorokiniana of barley.